Use of GIS and RS Combined with Artificial Intelligence Plate for Detecting and Analyzing of Aquatic Heavy Metals Threats for Environmental Sustainability of Green Ports - Usman Gabi, Alhassan; Mohamad Abdullah, Nazirah (Journal of Sustainable Natural Resources, 2023)
With the technological development globally, Geographic Information System and Remote Sensing (GIS) & RS has been used and reformed in providing reliable and useful data in the field of environmental studies advancement. There has been needed for GIS and RS in terms of biological and chemical elements in the aquatic environments to assess the concentration of trace metals in the tissue of aquatic species around the world. However, there is still inadequate information and exploration on the subject matter which calls for the use of artificial intelligence plates in acquiring data. There is a need for the use of the invented plate in green port sustainability in order to save time, money, life, less labour and availability of more multiple accurate data information that will have improved sustainability. The primary aim of this concept paper focused on using GIS & RS combined with artificial intelligence plate in Green port environmental sustainability to monitor, acquire data and identify biological and chemical elements data online for analysis. This aim was achieved by the application of qualitative research, that is synthetic literature review. Through the review, we are able to find out that artificial intelligence plates will be useful. Therefore, it requests for innovation of an artificial intelligent plate that will detect, analyze and recommend the concentration of heavy metals and other anthropogenic elements in the water bodies and species tissues without necessarily involving laboratory processes. In conclusion, to provide a theory from fusing past and present circumstances in order to forecast the future for coastal areas, GIS & RS applications and artificial intelligence plates were suggested. This review gives instances of GIS applications’ used in the stages of assessment, conservation, maintenance, sustainability, and protection of the environment of marine areas. This study suggests the use of a digital plate that can be used with GIS & RS in monitoring, spatiotemporal distribution and identifying the concentration of biological and chemical elements in the environmental sustainability of port institutions and industrial organizations.